Optical Measurement Mechanics - Wang, Kaifu (De Gruyter Textbook, 2018)
The book introduces the fundamentals of optical measurement mechanics, and discusses different types of interferometry, including (Digital) Holographic Interferometry, (Digital) Speckle Interferometry, Moiré Interferometry, Digital Image Correlation and Particle Image Velocimetry. It is an essential reference for graduate students, scientists and practitioners from both universities and research laboratories.